The Influence of Language Use toward the Implementation of Public Service Ethics - Mansyur Suma; Irwan Misbah; Somadi Sosrohadi; M. Dalyan (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This study investigates the role of language in the implementation of public service ethics, with a focus on Hajj services at the Ministry of Religious Affairs in Makassar City. It examines both verbal and non-verbal communication strategies used by public service professionals to understand how language influences ethical decision-making and interactions between service providers and the public. The research aims to explore how language choices support accountability, fairness, and transparency while encouraging ethical conduct in public institutions. Using a case study approach, the study concentrates on the interactions between Hajj service officers and prospective pilgrims during the registration, guidance, and procedural explanation stages. Data collection includes participatory observation of language use and non-verbal cues, such as gestures and intonation. The findings emphasize that key language characteristics like clarity, politeness, empathy, and motivational language play a crucial role in creating positive service experiences and promoting ethical behavior. The study concludes that strategic language use in public service fosters trust, transparency, and cooperation, enhancing relationships between service providers and the public and reinforcing a culture of accountability in public institutions.